Fat-Water Separation with High Temporal and Spatial Resolution for Abdominal MRI during Free Breathing - Ababneh, Riad; Benkert, Thomas; Breuer, Felix (Jordan Medical Journal, 2017)
Objective: To separate the fat and water contents in the abdomen during free breathing at hightemporal and high spatial resolution by employing radial sampling with a golden angleincrement.Materials and Methods: A radial fast imaging with steady-state free precession (TrueFISP)sequence was used and modified to allow for different echo times (TEs) for subsequent radialprojections for fat-water separation. The k-space-weighted image contrast (KWIC) radialfiltering technique was applied to enable high temporal as well as high spatial resolution.Finally, principal component analysis (PCA) was performed along the dynamic image seriesin order to reduce image streaking and enhance the signal-to-noise ratio (SNR).Results: The approach was combined with the KWIC filter and provided good fat-waterseparation with a robust high temporal (~100 ms) and high spatial resolution. Results for theabdomen with free breathing are presented.Conclusion: Good separation of fat and water signals was achieved using the radial TrueFISPsequence during free breathing